EXPERIMENTAL/CALIBRATION PROCEDURE OF PLASTIC SHEET TESTING MACHINE - Vidyanand Jakukore; Sachin Shinde; S.G.Mane; Pradnya Patil (International Journal of Innovations in Engineering Research and Technology, 2022)
In this work our main objective is to check the quality of plastic sheet paper of different companies and suggest best of one, so that farmers in India should know the quality and get awareness about the plastic sheet paper. This test method may be used to test all plastics within the thickness range described and the capacity of the machine employed. At this checking of tensile strength all size of sheet paper was performed. This tensile test measure the force required to break a specimen and extent to which the specimen stretches or elongate that braking point.